2021
DOI: 10.1371/journal.ppat.1009080
|View full text |Cite
|
Sign up to set email alerts
|

Balancing of the mitotic exit network and cell wall integrity signaling governs the development and pathogenicity in Magnaporthe oryzae

Abstract: The fungal cell wall plays an essential role in maintaining cell morphology, transmitting external signals, controlling cell growth, and even virulence. Relaxation and irreversible stretching of the cell wall are the prerequisites of cell division and development, but they also inevitably cause cell wall stress. Both Mitotic Exit Network (MEN) and Cell Wall Integrity (CWI) are signaling pathways that govern cell division and cell stress response, respectively, how these pathways cross talk to govern and coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Like in S. cerevisiae, the CWI MAPK pathway plays a critical role in regulating responses to cell wall stress in plant pathogenic fungi, and mutants deleted of the Slt2/Mps1 ortholog have increased sensitivities to cell wall lytic enzymes and cell wall stressors such as Congo Red (CR) or Calcofluor White (CFW) (Hamel et al 2012;Jiang et al 2018). Autolysis of aerial hyphae is observed in old cultures of the mps1 and bck1 mutants in M. oryzae and Aspergillus flavus (Xu et al 1998;Jeon et al 2008;Zhang et al 2020;Feng et al 2021). In S. cerevisiae, cell stressors, such as CR and Caspofungin, are sensed by the Mid2 and Wsc1 sensors (Jin et al 2013).…”
Section: Cell Wall Stressmentioning
confidence: 99%
“…Like in S. cerevisiae, the CWI MAPK pathway plays a critical role in regulating responses to cell wall stress in plant pathogenic fungi, and mutants deleted of the Slt2/Mps1 ortholog have increased sensitivities to cell wall lytic enzymes and cell wall stressors such as Congo Red (CR) or Calcofluor White (CFW) (Hamel et al 2012;Jiang et al 2018). Autolysis of aerial hyphae is observed in old cultures of the mps1 and bck1 mutants in M. oryzae and Aspergillus flavus (Xu et al 1998;Jeon et al 2008;Zhang et al 2020;Feng et al 2021). In S. cerevisiae, cell stressors, such as CR and Caspofungin, are sensed by the Mid2 and Wsc1 sensors (Jin et al 2013).…”
Section: Cell Wall Stressmentioning
confidence: 99%
“…Yin et al reported that the autophagy pathway directly affects spore germination and appressorium formation, thus influencing M. oryzae pathogenicity ( Yin et al, 2019 ). The CWI (cell wall integrity) maintenance mechanism was found to be a key factor in the pathogenicity of M. oryzae ( Feng et al, 2021 ), and there is crosstalk between CWI and autophagy pathways ( Yin et al, 2019 ). However, how is lipopeptide damage to the cell wall of M. oryzae related to autophagy?…”
Section: Discussionmentioning
confidence: 99%
“…The CWI signalling pathway plays an important role in responding to external stress and pathogenicity (Fuchs & Mylonakis, 2009; Herlaar & Brown, 1999; Nordzieke et al, 2019; Sanz et al, 2017; Willis et al, 2018). In M. oryzae , the CWI pathway consists of MoMkk1, MoMck1, and MoMps1, with MoMkk1 acting as a key element that mediates not only CWI but also various signalling pathways, such as autophagy (Yin et al, 2020), mitotic exit network (Feng et al, 2021), and the target of rapamycin pathway (Qian et al, 2018). However, the negative regulation of the CWI pathway and MoMkk1 in phosphorylation homeostasis has remained unexplored until now.…”
Section: Discussionmentioning
confidence: 99%
“…For protein kinase reaction, 2 μg of MoPtc1 or MoPtc2 was mixed with MoMkk1, MoMck1 in a kinase reaction buffer (100 mM phosphate‐buffered saline, pH 7.5, 10 mM MgCl 2 , 1 mM ascorbic acid; Sigma‐Aldrich), with the addition of 50 mM ATP (Sigma Aldrich). The subsequent experiments were performed according to the protocol (Feng et al, 2021; Jin & Gou, 2016; Yin et al, 2020; Yu et al, 2021).…”
Section: Methodsmentioning
confidence: 99%